2015
DOI: 10.1155/2015/739746
|View full text |Cite
|
Sign up to set email alerts
|

Acuteβ-N-Methylamino-L-alanine Toxicity in a Mouse Model

Abstract: The cyanobacterial neurotoxin β-N-methylamino-L-alanine (BMAA) is considered to be an “excitotoxin,” and its suggested mechanism of action is killing neurons. Long-term exposure to L-BMAA is believed to lead to neurodegenerative diseases including Parkinson's and Alzheimer's diseases and amyotrophic lateral sclerosis (Lou Gehrig's disease). Objectives of this study were to determine the presumptive median lethal dose (LD50), the Lowest-Observed-Adverse-Effect Level (LOAEL), and histopathologic lesions caused b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…DABA is a noncanonical amino acid structurally related to ornithine and lysine in that is has a side‐chain nitrogen (Figure ). It is produced by cyanobacteria alongside β‐ N ‐methylamino‐ l ‐alanine (BMAA) (Al‐Sammak, Hoagland, Cassada, & Snow, ; Fan, Qiu, Fan, & Li, ), a well‐known neurotoxin (Al‐Sammak, Rogers, & Hoagland, ; Cox et al, ; Cox, Davis, Mash, Metcalf, & Banack, ). As this is the major biological source of DABA and as DABA is always coexpressed with the highly toxic BMAA, determining the toxicity of DABA has not been a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…DABA is a noncanonical amino acid structurally related to ornithine and lysine in that is has a side‐chain nitrogen (Figure ). It is produced by cyanobacteria alongside β‐ N ‐methylamino‐ l ‐alanine (BMAA) (Al‐Sammak, Hoagland, Cassada, & Snow, ; Fan, Qiu, Fan, & Li, ), a well‐known neurotoxin (Al‐Sammak, Rogers, & Hoagland, ; Cox et al, ; Cox, Davis, Mash, Metcalf, & Banack, ). As this is the major biological source of DABA and as DABA is always coexpressed with the highly toxic BMAA, determining the toxicity of DABA has not been a high priority.…”
Section: Introductionmentioning
confidence: 99%
“…BMAA has, in fact, been linked to several neurodegenerative diseases, including Parkinson's, Alzheimer's and amyotrophic lateral sclerosis (ALS) [75]. A 2013 study linked an ALS cluster in Chesapeake Bay to consumption of BMAA-contaminated crabs [76].…”
Section: Bmaa and Als In Guammentioning
confidence: 99%
“…Lindstrom et al [ 31 ], while unable to demonstrate clinical signs of neurological abnormalities, observed abundant gliosis and pyknotic neurons surrounding the BMAA injection site as well as a dose-dependent loss of tyrosine hydroxylase (TH)-immunoreactive neurons and dendrites in the lesioned areas one week following intranigral or intracisternal injections of 10 μg or 400 μg BMAA to adult rats. However, although Al-Sammak et al [ 18 ] observed clinical symptoms in adult mice, such as myoclonus, convulsions, dragging gait, shaking and ataxia, following exposure to 2000 mg/kg body weight BMAA, and subsequently detected BMAA in the brain and liver tissue of all treated animals, histopathological examination of relevant brain tissue showed no histopathologic lesions in the brain. The livers, hearts, kidneys, lungs, and spleen tissue of BMAA-exposed animals were similarly unaffected.…”
Section: Introductionmentioning
confidence: 99%
“…Although some clinical signs of BMAA toxicity have been shown in chicks, rats and mice [ 9 , 18 , 19 , 20 , 21 , 22 , 23 ] with symptoms such as convulsions and ataxia being reported at high doses (4000 mg per kilogram body weight) [ 21 ], no animal model of BMAA toxicity has successfully reproduced all the neuropathological changes that are typically seen in AD, PD and/or ALS patients. Neither Polsky et al [ 24 ], nor Perry et al [ 25 ], nor Duncan et al [ 26 ] nor Cruz-Aguado et al [ 27 ] observed any clinical signs of toxicity, or biochemical or neuropathological abnormalities associated with the administration of BMAA to adult rats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation